Fungsi dan Peran Notaris Pada Peralihan Hak Atas Merek Melalui Perjanjian Jual-Beli - Putri, Maria Yohesti; Santoso, Budi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
A brand is a manifestation of a trade or service business. Apart from that, a brand is also an intangible object whose ownership can be transferred by transferring the rights to the brand through a notary. The role of the Notary in question is in making the brand transfer deed. Through this research, the authors aim to find out and examine how the function and role of a notary is in making a deed of transfer of rights to a brand through a sale-purchase agreement. In reviewing this journal, the author uses primary and secondary legal materials with a conceptual approach and applies normative juridical research methods which are carried out by examining the theories, concepts and laws and regulations concerned. The results of this study note that according to Law Number 20 of 2016 Concerning Trademarks and Geographical Indications Notarial (authentic) deed in transferring rights to a trademark through a sale-purchase agreement is not an obligation but can be used as an option or alternative. Notarial (authentic) deed has the best binding and evidentiary power, therefore a sale and purchase agreement using a Notarial deed is the best choice. Furthermore, the role of the Notary in terms of transferring rights to the mark through an agreement or sale is to provide understanding and legal protection by making authentic deeds which aim to provide legal certainty to the parties.